Protection of the Right to Information on One’s Health – A Non-Jurisdictional Form of Protection - Khodieieva, Nataliia; Yasynok, Mykola; Kuryliuk, Yurii; Filippov, Stanislav; Zemko, Alla; Yasynok, Dmytro (International Journal of Criminology and Sociology, 2021)
The article analyzes the theoretical aspects of protection as directly subjective civil rights and defines them within the framework of civil relations regarding the information on one's health. A clearer and complete description of the features of the realization of the right to information on one's health in the normatively established system of protection of subjective rights of a person has been obtained. It has been determined that the protection of the right to information on one's health is exercised freely, and the failure of a person to exercise the right to protection is not a ground for termination of this right. It is noted that during the protection of their violated right to health information, the authorized person may perform certain actions that are not related to the appeal to the competent state bodies and are a non-jurisdictional form of protection. The list of actions of an individual to protect the right to information on one’s health in the case of a non-jurisdictional form of protection of the above-mentioned right has been systematized.